초등 예비교사의 수학적 신념 변화에 관한 분석 - 김윤민(YUNMIN KIM); 류현아(Hyunah Ryu) (Suhak gyoyukak yeon-gu (Online), 2019)
초등 예비교사는 교사교육과정을 통해 수학 교사로 성장하고, 수학 교수학습에 대한 학생으로서의 경험에서 교사로서의 경험으로 이동할 수 있다. 이러한 과정에서 초등 예비교사가 지니는 수학적 신념은 변화한다. 본 연구는 초등 예비교사의 수학적 신념의 변화를 탐구하는 것을 목적으로 한다. 2015학년도, 2016학년도, 2017학년도 12월에 수학적 신념 검사 도구를 활용하여 동일한 연구대상에 설문조사를 실시하였고, 3년간 수학적 신념의 변화를 수학에 대한 신념, 수학 문제해결에 대한 신념, 수학 학습에 대한 신념, 수학적 자아개념에 대한 신념으로 범주화하여 살펴보았다. 또한 성별과 심화과정에 따라 수학적 신념의 차이가 있는지도 분석하였다. 연구 결과, 수학에 대한 신념과 수학 학습에 대한 신념은 변화가 있었지만, 수학 문제해결에 대한 신념은 변화가 없었다. 또한 자아개념에 대한 신념 중 유익성 요인과 선천적 능력 요인은 변화가 있었지만, 흥미 요인과 자신감 요인은 변화가 없었다. 둘째, 심화과정에 따라 수학적 신념은 고정관념 요인, 과정 요인, 흥미 요인, 자신감 요인에서 차이가 나타났고, 성별에 따른 수학적 신념의 차이는 도전성 요인, 교사주도 요인, 유익성 요인, 자신감 요인에서 나타났다. 이러한 결과를 바탕으로 초등 예비교사의 교육프로그램 및 교육과정에 시사점을 줄 것이다. Elementary pre-service teachers can be educated as mathematics teachers through the teacher curriculum, and can move from the student’s experience in mathematics teaching and learning to the teacher's experience. In this process, the mathematical beliefs of elementary pre-service teachers change. The purpose of this study was to investigate the change of mathematical beliefs of elementary school pre-service teachers. The same subjects were surveyed by the Mathematical Belief in December 2015, 2016, and 2017, and the changes in mathematical beliefs were examined for three years. Specifically, we examined categorical changes in mathematical beliefs over three years into beliefs in mathematics, in solving problems, in mathematics learning, and in mathematical self-concepts. We also examined the differences in mathematical beliefs according to gender and major. As a result, beliefs in mathematics and in mathematics learning have changed, but beliefs in mathematical problem-solving are unchanged. Also, among the beliefs about self-concept, usefulness and innate ability have changed, but interest and confidence have not changed. Second, mathematical beliefs differed in stereotypes, process factors, interest factors, and confidence factors according to majors, and differences in mathematical beliefs according to gender were found in challenge, teacher-led, usefulness, and confidence factors. These results provide implications for the educational programs and curriculum of elementary pre-service teachers. KCI Citation Count: 0